Adjacent and diagonal coupling mechanism by even-branched resonator for adjustable radiometric filtering applications - Hossain, A.K.M. Zakir; Azam, S.M. Kayser; Othman, Mohamadariff; Ibrahimy, Muhammad I.; S.M.A. Motakabber; Islam, Md. Shazzadul (Elsevier Ltd, 2022)
Radio frequency-based measurement components utilize differently designed resonators to adjust various filtering characteristics. We introduce a unique coupling mechanism of a novel even-branched resonator that alone can adjust 6 radiometric filtering characteristics i.e., bandpass operation, harmonic suppression, quality-factor enhancement, switching ability, tunability, and digitized coupling. In our design, even-branched resonators have inter-resonator magnetic coupling while each end of their branch-lines has intra-resonator electrical coupling. Using the prominent magnetic coupling, adjacently coupled- and diagonally coupled- resonators are developed. A short-circuited stepped-impedance parallel technique is applied to achieve enhanced quality-factor and switchable/tunable bandpass filtering features. Characteristics of our radiometric resonator are determined by the odd/even dependency on its branch number. Our resonator couples with its another identical unit only when it has an even number of branches and is coupled by branch-lines that are also even-numbered. With novel digitized coupling characteristics, our resonator provides a 6-in-1 solution for intelligent radiometric systems.